Effect of shear stress alteration on atherosclerotic plaque vulnerability in cholesterol-fed rabbits. (April 2014) - den Dekker, Wijnand K; Tempel, Dennie; Speelman, Lambert; Huizingh, Jeroen; Ramos, Allan; Gijsen, Frank J; Wentzel, Jolanda J; Cheng, Caroline; Duckers, Henricus J
Previously, we created an experimental murine model for the induction of vulnerable plaque (VP). Although this murine model offers the opportunity to study the different molecular biological pathways that regulate plaque destabilization, the size of the animals severely limits the use of the model for in vivo diagnostics and percutaneous interventions. This study aimed to create a VP model in the rabbit, based on the murine model, to aid the assessment and development of novel diagnostic and interventional tools. New Zealand white rabbits were fed on a 2% cholesterol diet. After 1 week, a shear stress-altering device was implanted around the right carotid artery. Twelve weeks after cast placement, the carotid artery was isolated and processed for (immuno-)histological analysis to evaluate the presence of a VP phenotype. Atherosclerotic plaques with high lipid and macrophage content, low vascular smooth muscle cell content and intimal neovascularization were located upstream and downstream of the cast. The plaques lacked a significant necrotic core. In conclusion, we were able to create atherosclerotic plaques with a phenotype beyond that of a fatty streak, with a high percentage of lipids and macrophages, a thick cap with some vascular smooth muscle cells and neovascularization. However, as there was only a small necrotic core, the overall phenotype seems less vulnerable as compared to the thin fibrous cap atheroma in patients.